2021
DOI: 10.3389/fmicb.2021.716307
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Prebiotic Effect of Bread-Making Process in Inflammatory Bowel Disease Microbiome

Abstract: Inflammatory bowel disease (IBD), including its two main categories (Crohn's disease and ulcerative colitis), has been linked both to gut microbiota and to diet. Bread is a daily food that has a potential capacity as a prebiotic. Our aim was to evaluate different bread-making processes and their effect on fecal colonic microbiota in IBD patients. The microbial composition of several sourdoughs and dough samples was analyzed by high-throughput sequencing of 16S and 18S rRNA genes. Three types of bread, which fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 97 publications
0
5
1
Order By: Relevance
“…While prior research has suggested that dietary components like sourdough, long-fermentation, whole-grain flour, and sodium content [79,80] could potentially influence gut microbiota [34,[36][37][38][39], our present study did not yield significant shifts in the gut microbiome. The differential abundance analyses conducted in the present study did not reveal any taxa showing significant differences after the dietary intervention at any taxonomic level analyzed.…”
Section: Microbiota Differential Abundances and Diversitycontrasting
confidence: 76%
See 3 more Smart Citations
“…While prior research has suggested that dietary components like sourdough, long-fermentation, whole-grain flour, and sodium content [79,80] could potentially influence gut microbiota [34,[36][37][38][39], our present study did not yield significant shifts in the gut microbiome. The differential abundance analyses conducted in the present study did not reveal any taxa showing significant differences after the dietary intervention at any taxonomic level analyzed.…”
Section: Microbiota Differential Abundances and Diversitycontrasting
confidence: 76%
“…In addition, it has been observed that sourdough, long-fermentation and whole-grain flour might modulate gut microbiota and lower systematic inflammation [34,36,38,39]. Finally, in a previous work of our group, in vitro experiments characterized the potential of different types of bread to modulate stool microbial composition in IBD patients towards a microbiota profile closer to healthy subjects [37].…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…Dysgonomonas and Butyricicoccus were considered to be potential probiotic bacteria [34,35]. Roseburia and Ruminococcus could produce short chain fatty acids [36,37]. The short chain fatty acids were fermented by some gut microbiota and played an important role in gut health [38].…”
Section: Discussionmentioning
confidence: 99%